RustMapper: White Pine Blister Rust Risk Across High Elevation Forests in the Western United States - Sparkle L. Malone; Anna W. Schoettle; Kelly S. Burns; Holly S. J. Kearns; Jane E. Stewart; Maria Newcomb; Christy M. Cleaver (Scientific Data)
Abstract White pine blister rust (WPBR) is one of North America’s most damaging tree epidemics. Aggregating data from more than 80 independent studies across the western U.S. from 1995–2024, we estimate WPBR risk for high-elevation five-needle pine species (High-5) from 1980–2023 in the adaptive management tool RustMapper. WPBR risk is the probability of observing WPBR on the High-5. Stream density, topography, hardiness zone, precipitation, air temperature, vapor pressure deficit, and relative humidity were critical in estimating WPBR risk. WPBR risk increased with moisture and declined with temperature. Across the High-5 range, suitable conditions were found in areas where the disease had not yet invaded and throughout regions where the disease was well established. As a result, the mean risk for WPBR was much higher in the north (~0.6) compared to the southern portions of the High-5 range (~0.15). These findings indicate cautious optimism for disease mitigation success in regions where the disease is established and urgency for proactive management where WPBR occurrence is currently low.